Effect of Temporal and Spatial Myopia on Managerial Performance - Abbas Gatea Atiyah (Newinera Publisher, 2022)
An important role played by the strength of a company's position in the industry, companies must examine the factors that hinder building their strategic position. Companies need to have a successful management performance. It is the process of planning, organizing, and directing tasks, as well as monitoring the implementation of tasks. Therefore, this study aimed to explore the size of the obstacle posed by spatial myopia and temporal myopia in weakening the ability of organizations to achieve successful managerial performance. Where this is embodied in the hypotheses of the study, which state: There is an effect of spatial myopia and temporal myopia in achieving successful managerial performance. Therefore, the hypotheses of the study were tested in one of the important institutions in the oil sector (the petroleum products distribution company in Thi-Qar Governorate). The test was conducted on a sample of (132) managers from all managerial levels in the company. The research model and its hypotheses were tested using SmartPLS. The results of the study showed that there is an effect of spatial myopia and temporal myopia on the performance of organizations. So the study made some conclusions about how to treat. And the transition to adopting the concept of managerial hyperopia is one of the useful tools for the success of the organization's performance.